Histopathological analysis of hysterectomy specimens in a tertiary care centre: study of 160 cases - Jandial, Roopali; Choudhary, Mehnaz; Singh, Kuldeep (International Surgery Journal, 2019)
Background: Hysterectomy is the most commonly performed gynaecological surgery as the female reproductive system has been affected by various non-neoplastic and neoplastic conditions during the life time of a woman. Methods: This retrospective study was conducted on 160 hysterectomy specimens reported to Department of Pathology. They were compared in terms of age of the patients and pathology of hysterectomy specimens. The histopathological findings of hysterectomy specimens was noted and these findings were then correlated with clinical diagnosis. The aim of the study was to evaluate the wide range of pathological lesions, commonest pathology involved and correlation of the preoperative clinical diagnosis with the histopathological diagnosis in the hysterectomy specimens. Results: The most common type of hysterectomy was total abdominal hysterectomy with bilateral salpingo-ophorectomy with 102 cases (63.7%). Peak incidence at 5th decade of life in 92 cases (57.5%) was noted. The most common clinical indication was fibroid uterus in 81 cases (50.6%). Proliferative phase of endometrium was the commonest finding in 87 cases (54.3%). In case of myometrium, 95 leiomyomas were noted. On histomorphological study of cervical lesions, chronic cervicitis was commonest finding in 75 (46.8%) cases. Conclusions: Few double pathologies can be missed clinically so clinico-pathological correlation in all cases of hysterectomy has been proved to be important to improve the clinical outcome and post-operative management.